A Bayesian model of knightian uncertainty - Nabil I. al- Najjar; Jonathan Weinstein (Institute for Advanced Studies (IHS), 2013)
A long tradition suggests a fundamental distinction between situations of risk, where true objective probabilities are known, and unmeasurable uncertainties where no such probabilities are given. This distinction can be captured in a Bayesian model where uncertainty is represented by the agent's subjective belief over the parameter governing future income streams. Whether uncertainty reduces to ordinary risk depends on the agent's ability to smooth consumption. Uncertainty can have a major behavioral and economic impact, including precautionary behavior that may appear overly conservative to an outside observer. We argue that one of the main characteristics of uncertain beliefs is that they are not empirical, in the sense that they cannot be objectively tested to determine whether they are right or wrong. This can confound empirical methods that assume rational expectations.
Keywords: A10; A80; 330; Knightian uncertainty; consumption smoothing; uncertainty premium; rational expectations; Haushaltseinkommen; Konsumentenverhalten; Entscheidung bei Unsicherheit; Rationale Erwartung; Bayes-Statistik; Theorie